Characterization of Zircaloy-4 after Gaseous Hydriding at the Temperature Range of 350-600°C - R. Sigit; H. Suwarno; B. Soegijono (Atom Indonesia, 2016)
The degradation of the mechanical properties of zircaloy-4 as nuclear fuel cladding is inevitable due to its interaction with hydrogen during normal reactor operation. This experiment observed the occurence of hydride phases after gaseous hydriding with hydrogen at elevated temperature, and their effects were evaluated based on the material's microstructure and mechanical properties. The zircaloy-4 cladding materials were annealed for two hours. It was followed by hydriding with the pressure from 100 up to 1200 mbar at various temperatures of 350°C, 500°C,550°C and 600°C. The pressure-composition-isotherm (PCI) diagram showed that the hydrogen absorbed by specimen namely 0.18% wt, 0.38% wt, 0.44% wt and 0.74% wt at 350°C, 500°C, 550°C and 600°C, respectively. This result confirmed that the hydrogen content were 10, 128, 250, and 1357 ppm at 350°C,500°C,550°C, and 600°C, respectively, as measured by an ONH analyzer. X-ray diffraction showed that δ-hydride peaks were very weak based on fitting with the hydride database. The results from optical microscope and scanning electron microscope confirmed the presence of hydrides at the specimens, identified by the growth of needle-like structure at those temperatures.Received: 5 January 2016; Revised: 15 June 2016; Accepted: 20 August 2016